Early repolarization pattern associated with coronary artery disease and increased the risk of cardiac death in acute myocardium infarction - Fan, Jun; Yao, Feng‐Juan; Cheng, Yun‐Jiu; Ji, Cheng‐Cheng; Chen, Xu‐Miao; Wu, Su‐Hua (Annals of noninvasive electrocardiology, 2020)
Background Early repolarization pattern (ERP) was associated with sudden cardiac death in recent studies. However, the associations between ERP and coronary artery disease (CAD), and ERP and cardiac death caused by acute myocardial infarction (MI) remains unclear. Methods We retrospectively enrolled consecutive 1,545 CAD patients and 908 non‐CAD subjects as control group which were confirmed by coronary angiograph. The CAD patients include stable CAD, acute MI patients, and old MI patients. Multivariate logistic regression was employed to evaluate the relationship between ERP and CAD, and ERP and cardiac death caused by acute MI. Results Of the 1,545 CAD subjects, there were 1,029 stable CAD patients, 404 acute MI patients, and 112 old MI patients. The incidence of ERP was much higher among patients with CAD than without CAD subjects (20.1% vs. 6.2%, p < .001) after adjusting for major cardiovascular risk factors. No significant correlation was observed between lead region of ERP on 12‐lead ECG and single abnormal artery. Of the 404 acute MI patients, 342 patients survived and 62 patients died. Incidence of ERP was higher in non‐survivor than survivor patients with acute MI (24.2% vs. 17.5%, p = .006) after adjustment for major cardiovascular risk factors. Conclusion The incidence of ERP was higher in CAD patients than subjects without CAD and in non‐survivor patients than survivor patients with acute MI. The lead region of ERP on 12‐lead ECG was not associated with single abnormal coronary artery.